PRAGMALINGUISTIC AND LINGUOCULTURAL FEATURES OF ADVERTISING SLOGANS IN ENGLISH (SCIENCE TIME JOURNAL, 2026)
This article investigates the pragmalinguistic and linguocultural features of English advertising slogans. It focuses on how slogans compress commercial value into short verbal formulas through imperative force, evaluation, metaphor, rhythm, alliteration, and identity appeals. A selected corpus of internationally recognizable slogans is analysed to show how cultural codes, symbolic meanings, and audience expectations shape persuasive effect. The findings indicate that the most efficient slogans do not merely describe products; they verbalize consumer experience, value orientation, and selfpositioning.